Candida tropicalis endocarditis: Treatment in a resource-poor setting - Kumar Prashant; Muranjan Mamta; Tullu Milind; Vaideeswar Pradeep; Kher Archana; Lahiri Keya (Wolters Kluwer Medknow Publications, 2010)
Fungal endocarditis (FE) is rare in children and does not usually occur in structurally normal hearts. The commonest causative agent is Candida albicans. We report a 5-year-old female child presenting with high-grade fever and cardiac failure. Anemia, leukocytosis and high CRP were found, but bacterial blood culture was sterile. There was no response to antimicrobial agents. Two-dimensional echocardiography revealed a large heterogeneous mass attached to the right ventricle and tricuspid valve. Provisional diagnosis of FE was made, which was confirmed by growth of Candida tropicalis in blood culture. Liposomal amphotericin B was started, followed by radical curative surgery including excision of the entire vegetation with total tricuspid valve excision. Histopathology and culture of the resected vegetation confirmed the diagnosis. The patient was given antifungal therapy for a total of 7 weeks, including 2 weeks of post-operative treatment, following which she was afebrile.